Contribution of cork oak plantations installed after 1990 in Portugal to the Kyoto commitments and to the landowners economy - Coelho, Marta Baptista; Paulo, Joana Amaral; Palma, João Henrique Nunes; Tomé, Margarida (Forest Policy and Economics, 2012)
Cork oak stands are a part of the agroforestry ecosystem in Portugal, characterized by a low crown cover from cork oak trees, managed towards cork production, and sometimes in combination with grazing. In recent years, European Union policies gave impetus to a large area of new cork oak plantations, which have been established mainly for cork production purposes, and consequently with higher stand density than traditional agroforestry systems. These plantations are important not only for cork production but also for the carbon sequestered by these slow growing forests that won't be harvested for wood production. Thinning operations will be needed to avoid excessive inter-tree competition and wood extracted from these thinning may also provide income for the owners. In the present study, carbon sequestered and wood volumes resulting from thinning were estimated for the next 70 years. Three scenarios of different annual afforestation rates and different site indexes were tested. The resulting values for the considered scenarios show that, if the plantation rates are maintained, new cork oak plantations will have an important contribution to the Portuguese commitments to providing CO2 offsets under the Kyoto protocol. Additionally, due to the increasing values of initial density in new cork plantations, cork oak forests will produce a signiﬁcant volume of wood that may become an important contribution to the landowners' income.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Carbon Sequestration; Cork oak; Kyoto protocol; New plantations area; Wood

Silviculture and Carbon Sequestration in Mediterranean Oak Forests - Cañellas, I; Sanchez-Gonzalez, M; Bogino, S M; Adame, P; Herrero, C; Roig, S; Paulo, J A; Bravo, F (Managing Forest Ecosystems: The Challenge of Climate Change, 2008)
The Kyoto Protocol requires every industrialized country to have a transparent and verifiable method for estimating the size and evolution of the carbon stored in forest ecosystems. The intergovernmental panel on climate change (IPCC, 2007) predicts the evolution of the stock over the first commitment period (2008–2012) using the “bottom-up approach”. This approach is based on the use of data from national or regional forest inventories. The biomass of living trees including their dead parts comprises the main carbon pool in forest ecosystems along with the biomass of understorey plants, litter, woody debris and soil organic matter (Pignard et al., 2004). The objective of this chapter is to present some of the studies currently being carried out in Spain and Portugal which are concerned with the possibility of estimating the amount of carbon fixed by two of the main oak species in the Iberian Peninsula; rebollo oak (Quercus pyrenaica Willd.) and cork oak (Quercus suber L.). Three different methodological approaches have been used. The first approach is to use growth models to evaluate the carbon sequestration in both cork and wood over the life of a cork oak plantation. This approach has been applied both for Spain and Portugal. The second approach involves using a yield table as a tool to estimate the carbon sequestration in Quercus pyrenaica forests based on Spanish National Forest Inventories. In a third approach, data from a network of plots is used to estimate the carbon sequestration in pure and mixed Quercus pyrenaica forests. The application of these different methodologies would allow us to forecast and improve the carbon sequestration in oak forests as well as increasing our understanding of their dynamics.
Keywords: biomass; carbon stock; Kyoto protocol; Portugal; Spain

Silviculture and Carbon Sequestration in Mediterranean Oak Forests - Cañellas, I.; Sánchez-González, M.; Bogino, S. M.; Adame, P.; Herrero, C.; ROIG, S.; Paulo, J. A.; Bravo, F. (Managing Forest Ecosystems: The Challenge of Climate Change, 2008)
The Kyoto Protocol requires every industrialized country to have a transparent and verifiable method for estimating the size and evolution of the carbon stored in forest ecosystems. The intergovernmental panel on climate change (IPCC, 2007) predicts the evolution of the stock over the first commitment period (2008–2012) using the “bottom-up approach”. This approach is based on the use of data from national or regional forest inventories. The biomass of living trees including their dead parts comprises the main carbon pool in forest ecosystems along with the biomass of understorey plants, litter, woody debris and soil organic matter (Pignard et al., 2004). The objective of this chapter is to present some of the studies currently being carried out in Spain and Portugal which are concerned with the possibility of estimating the amount of carbon fixed by two of the main oak species in the Iberian Peninsula; rebollo oak (Quercus pyrenaica Willd.) and cork oak (Quercus suber L.). Three different methodological approaches have been used. The first approach is to use growth models to evaluate the carbon sequestration in both cork and wood over the life of a cork oak plantation. This approach has been applied both for Spain and Portugal. The second approach involves using a yield table as a tool to estimate the carbon sequestration in Quercus pyrenaica forests based on Spanish National Forest Inventories. In a third approach, data from a network of plots is used to estimate the carbon sequestration in pure and mixed Quercus pyrenaica forests. The application of these different methodologies would allow us to forecast and improve the carbon sequestration in oak forests as well as increasing our understanding of their dynamics.
The following values have no corresponding Zotero field: periodical: Managing Forest Ecosystems: The Challenge of Climate Change, electronic-resource-num: 10.1007/978-1-4020-8343-3
Keywords: biomass; carbon stock; Kyoto protocol; Portugal; Spain